Pengaruh Perencanaan Pajak, Beban Pajak Tangguhan dan Aset Pajak Tangguhan Terhadap Manajemen Laba Pada Perusahaan Sektor Infrastruktur, Utilitas dan Transportasi Yang Terdaftar di Bursa Efek Indonesia - Kezia A.M Silalahi; Emi Masyitah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
Earnings management is an intentional action taken by management that leads to a desired level of profit. Earnings management can be performed by companies by increasing or decreasing profits according to the motivations or objectives of the company in performing earnings management. This study aims to examine the effect of Tax Planning, Deferred Tax Expense, and Deferred Tax Assets on Earnings Management. The research was conducted in the infrastructure, utilities, and transportation sectors that have been listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. In determining the sample, purposive sampling method was used, resulting in a sample size of 28. The data analyzed in this study used multiple linear regression analysis. Based on the findings, it was found that Tax Planning and Deferred Tax Expense do not have an effect on Earnings Management, while Deferred Tax Assets do have an effect on Earnings Management.